Mengakomodasi Kebutuhan Rohani Anak Berkebutuhan Khusus di GBI Bethel Bandung - Wihardja, David Aripin; Hermanto, Yanto Paulus (Sekolah Tinggi Teologi Sola Gratia Medan, 2025)
Abstract. The problem of children with special personalities should be our common concern because they also have the right to life and attention and need to grow and develop fully according to the dignity and human dignity that God has given them. As holistic creatures, they also need attention not only in terms of physiology, but also in terms of their spirituality. Children with special needs are often a burden for their parents because many parents do not understand how to educate these children, especially spiritually. The researcher in this case conducted research at the church where the researcher worships because the worship of children with special needs has started in Sunday school. The problem studied is about the follow-up of the worship of children with special needs and aims to improve the spirituality of children with special needs. The research methodology used is a qualitative method with a field survey involving direct data collection at the research location, such as through observation, interviews, and group discussions. From the research, it was found that the worship of children with special needs can improve children's spirituality and foster a sense of sociality among children with special needs. The results of the study will be applied at the Bethel Indonesia Church in Bandung. Abstrak. Masalah anak berkepribadian khusus akhir-akhir ini mencuat lagi ke permukaan , dikarenakan dengan kemajuan zaman dan obat-obatan. Anak- anak berkebutuhan khusus sering menjadi beban bagi orang tuanya dikarenakan banyak dari orang tua yang tidak mengerti bagaimana cara mendidik anak-anak tersebut terutama secara rohani. Peneliti dalam hal ini melakukan penelitian baik secara langsung di gereja tempat peneliti beribadah karena ibadah anak berkebutuhan khusus sudah dimulai di sekolah minggu. Masalah yang diteliti adalah tentang penindak lanjutan dari ibadah anak berkebutuhan khusus tersebut dan tujuan adanya peningkatan kerohanian pada anak-anak tersebut, dapatlah dismpulkan bahwa usulan dari peneliti dapat dilakukan di Gereja Bethel Indonesia Bandung.